Successful one stage operation for a synchronous, duodenal carcinoma, colonic carcinoma and renal oncocytoma in an adult patient - Faraj, Walid (BioMed Central, 2011)
We report a rare case of synchronous duodenal carcinoma, colonic carcinoma and renal oncocytoma successfully treated using a one-stage surgical approach. Potential risk factors for multiple primary malignancies associated with duodenal carcinoma are discussed. This case illustrates several practice points for consideration: 1. Patients presenting with small intestinal carcinomas have a higher than average chance of developing second primary tumors in other organs; this should be taken into consideration during staging and follow-up. 2. For full staging of patients presenting with small bowel tumors, upper and lower gastrointestinal endoscopy and PET scanning should be considered. 3. A one-stage surgical procedure can be used safely and successfully for multiple synchronous primary tumors.